Cesarean rate and its related factors in - Khosravi, M; Armat, MR; Khadem, N (Advances in Nursing & Midwifery, 2008)
Background According to the WHO, no region in the world can justify the Cesarean rate higher than 10-15%. However, statistics of most areas over the world show a great discrepancy with this figure. There has been a gradual increase in Cesarean births over the past 30 years with greater risk for maternal health, lengthier recovery, more cost, and increased mortality rate. Some authorities believe that over half of the Cesareans are unnecessary. Purpose This descriptive correlational study was conducted to determine the rate and related factors of Cesarean birth in Bojnurd. Methods 473 singleton mothers delivering matured term newborns over 2500 gr. were selected. Delivery type was considered as a dependent variable whereas 20 other variables mainly associated with socioeconomic status of family and characteristics of mothers as well as infants were considered as independent variables. Data were collected by a questionnaire, measurement of infants’ head circumference and interview with mothers. Content and test-retest methods were used respectively to validate and made the tool reliable (r=0.7). Results Cesarean birth rate in Bojnurd was 25.4% and was positively correlated with better job position and parents’ level of education (p<0.006), urbanism (p=0.001), less family members (0.008), newborns weighing 3900 grams or more (p=0.0.55), greater head circumference (p=0.0), heavy prenatal weight (p=0.013), and higher maternal age (p=0.054). Conclusion With respect to increased Caesarian rate in mothers with better socioeconomic status and higher age, it seems that providing appropriate educational plans for families and decreasing marital age by national planning may decrease the rate. Keywords Cesarean, Delivery type, Cesarean rate